Accelerometers as a tool for analyzing the biomechanics of ice hockey skating - Stetter, B.; Buckeridge, E.; LeVangie, M.; Nigg, S.; Nigg, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Despite ice hockey`s widespread popularity, the biomechanical contributions to successful skating performance is poorly understood (Lafontaine, 2007). This lack of knowledge may be explained by the difficulty of collecting data on ice (Upjohn et al., 2008). Therefore, the primary aim of this study was to use simple, lightweight accelerometers as a viable means of biomechanical data collection on ice. A secondary aim was to use data derived from accelerometers to quantify stride timing characteristics and whole body intensity during forward skating. Methods Twenty four ice hockey players of three levels of ability were equipped with two 3D accelerometers as they performed 30 m skating sprints on an ice rink. The first 10 m were considered the acceleration phase while the final 10 m were considered the maximum velocity phase. Temporal stride information (i.e. total stride time and ice-contact time) was extracted form the first accelerometer, located on the center of the skate chassis. The second accelerometer, fixed to the skin overlying the 5th lumbar vertebra was used to estimate whole body intensity of a skating stride (i.e. stride intensity). Timing lights were set up in order to obtain overall sprint times as a performance variable. Two-way ANOVAs were used to compare player caliber (high, medium, low) and stride type (acceleration and maximum velocity). Pearson`s correlations were calculated to identify relationships with performance. Results: Acceleration strides had a significantly shorter stride time, shorter contact time and a higher stride intensity compared to maximum velocity strides (p<0.05). When comparing participant abilities, high caliber players had significantly shorter contacts time than low caliber players, in addition to a significantly higher stride intensity than both medium and low caliber players (p<0.05). A negative correlation between stride intensity and total sprint time was found, indicating that sprint times decrease as stride intensity increases. Discussion: The significant differences between stride types support the notion that as a skater increases their speed, their skating motion changes (Lafontaine, 2007). Higher stride intensities found for high caliber players, as well as the negative correlation between stride intensity and total sprint time suggests that high performance is related to greater effort. Future research should attempt to apply this new approach to other skating movements to both detect temporal skating patterns and advance the understanding of the biomechanics of ice hockey skating.